2019
DOI: 10.9745/ghsp-d-19-00026
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Satisfaction With and Perceptions of the Quality of Postabortion Care at Public-Sector Facilities in Mainland Tanzania and in Zanzibar

Abstract: Tanzanian women expressed greater satisfaction with postabortion care received at district hospitals and health centers, where they experienced shorter waiting times, more family planning counseling, and threefold greater voluntary uptake of family planning, than at regional hospitals. Continued decentralization to district hospitals would likely enhance client satisfaction with postabortion care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 29 publications
4
38
0
5
Order By: Relevance
“…Our results also suggest that supply-side strategies can help providers strengthen the quality and integration of family planning with treatment for postabortion complications 14 . Findings from exit interviews with PAC clients revealed that over two-thirds of participants did not recall receiving any counseling on family planning services during their receipt of PAC and that fewer than one-fifth received a contraceptive method 5 . In response to these findings, providers expressed that organizational challenges, such as limited facility space and lack of time and in-service training opportunities, undermined their ability to more effectively provide contraceptive counseling and services within PAC.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our results also suggest that supply-side strategies can help providers strengthen the quality and integration of family planning with treatment for postabortion complications 14 . Findings from exit interviews with PAC clients revealed that over two-thirds of participants did not recall receiving any counseling on family planning services during their receipt of PAC and that fewer than one-fifth received a contraceptive method 5 . In response to these findings, providers expressed that organizational challenges, such as limited facility space and lack of time and in-service training opportunities, undermined their ability to more effectively provide contraceptive counseling and services within PAC.…”
Section: Discussionmentioning
confidence: 69%
“…The study included exit interviews with women who had just received PAC. This study, conducted among 412 PAC clients, found that 69.9% of participants could not recall receiving any information on contraception from their PAC provider, and 82.6% left facilities without a modern contraceptive method 5 …”
Section: Introductionmentioning
confidence: 90%
“…The authors describe progress in providing a broad range of family planning methods, including long-acting reversible contraceptives (LARCs); highlight new technologies for communication; document the perspectives of patients and providers, including their views on what is still needed to optimize PAC services; and identify cost-effective strategies for governments, programs, and donors 10 14 …”
Section: Postabortion Family Planning: What Work?mentioning
confidence: 99%
“…The authors also document that misunderstanding and misconceptions about contraceptives remain a major stumbling block in providing the family planning component of PAC to clients; that training in counseling and values clarification is much needed; and that engaging men to support family planning for their partners is important and can be challenging 6 10 , 12 , 14 16 …”
Section: Postabortion Family Planning: What Work?mentioning
confidence: 99%
See 1 more Smart Citation